Voluntary program to reduce soot. (29th January 2013) - Showstack, Randy
Abstract : The U.S. Environmental Protection Agency (EPA) announced on 17 January that it has formulated a voluntary clean air program, Particulate Matter (PM) Advance, to help communities develop strategies to reduce fine‐particle emissions, often called soot or particulate matter, that can be harmful to human health.